Analisis Bahasa Melayu dalam Cerita Rakyat Melayu Riau: Kajian Morfologi - Erma Aryanti, Ade; Mukhlis, Muhammad (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
The Bengkalis dialect of Riau Malay is unique. In Indonesian, the prefix ter- meets basic words that start with /l/, so there will be a conservation of phonemes, for example {ter-} + {then} = {too} "too". This research belongs to the type of qualitative research. The method used is descriptive method, namely by first collecting data and then describing it, then analyzing and interpreting it based on the method set by the author. Based on the results of the analysis and discussion in this study, it can be concluded that the affixes contained in the Malay language in the Folktale Khayal Interview with Yung Dollah by Hang Kafrawi are prefixes, suffixes and confixes. The Malay prefixes in Yung Dollah's interview story consist of {meN-}, {me-}, {ber-},{mem-},{se-}, {ter-}. Suffixes in Malay In folklore Interview Khayal Yung Dollah consists of {-an}. Confixes in Malay in the story Interview with Khayal Yung Dollah consist of { maN-},{ka-an}, which are found in Malay In Folktales with Khayal Yung Dollah Interview only {be-}, where the prefixes {be-} and { are not found ber-} prefix te-consisting of {te-} and {ter-} found in Malay in Yung Dollah folklore. The forms of Malay affixes in folklore interviews with Khayal Yung Dollah that are commonly found are the prefixes {ber-}, {meN-}, {me-}, te-},{se-}. So the prefixes {ber-}, {meN-}, {mem-} are productive forms of affixes, while the affix forms that are rarely found are suffixes {-an} which are rarely found in Malay in Yung Dollah Folklore. So the suffix {-an} is unproductive.